Acceptance and coverage of fast invitation methods to in-the-moment surveys. (September 2022) - Ochoa, Carlos; Revilla, Melanie
When asking survey participants about past events, respondents might not properly recall the requested information. Surveying participants right when an event of interest occurs should reduce these recall errors. Such "in-the-moment surveys" are used nowadays but only in very specific occasions. Online panels that ask their members to share their online behaviors (metered panels) offer a new opportunity to use in-the-moment surveys whenever an online event of interest is detected. Previous research shows that the willingness to participate in in-the-moment surveys is notably high in metered panels, but even panellists willing to participate may fail to do so if they do not see the invitation in time. Very little is known about how participants perceive the different invitation methods available. A survey of members of a metered panel in Spain reveals that invitation methods deployed on smartphones get higher levels of acceptance and coverage, and are perceived as fastest. Moreover, offering several invitation methods on different devices would maximize the opportunities to participate in time, making them more feasible.